2013
DOI: 10.1177/1420326x13501097
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of air cleaning technologies existing in the Danish market: Experiments in a duct and in a test room

Abstract: Five portable air cleaning technologies including one new technology were evaluated to find their effectiveness in removing ultrafine particles. Measurements were carried out both in a duct and in a test room. The results showed that the technologies that use/create ozone to clean air can increase the ozone level significantly in the room. Moreover, they can cause generation of ultrafine particles and consequently increase ultrafine particle concentration in the room. The study suggests using a mechanical filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In order to reduce indoor particle concentration, more and more air cleaners have been used and many researchers have investigated their performances. 46 According to a review article by Nazaroff, 7 the indoor particle transport is influenced by many factors including the particle category, clean air delivery rate (CADR), room geometry, roughness of room surfaces and thermal plume generated by human bodies or other devices. There exist many experimental or numerical investigations on these issues, 810 but most studies on the removal ability of air cleaners usually assumed that the air mixing in indoor environment is perfect and contaminant concentration is uniformly distributed, which means the location of the air cleaner has no effect on its particle removal efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce indoor particle concentration, more and more air cleaners have been used and many researchers have investigated their performances. 46 According to a review article by Nazaroff, 7 the indoor particle transport is influenced by many factors including the particle category, clean air delivery rate (CADR), room geometry, roughness of room surfaces and thermal plume generated by human bodies or other devices. There exist many experimental or numerical investigations on these issues, 810 but most studies on the removal ability of air cleaners usually assumed that the air mixing in indoor environment is perfect and contaminant concentration is uniformly distributed, which means the location of the air cleaner has no effect on its particle removal efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Indoor air quality is closely related to human health since most people spend nearly 90% of lifetime in the indoor environment (Klepeis et al 2001). Both gaseous contaminants and fine particles in the indoor air can pose a threat to human health (Ardkapan et al 2014;Cao and Meyers 2015). The severe acute respiratory syndrome (SARS) exploded in 2003 was a typical epidemic disease that infects human by the tiny droplets or particles carrying various virus and bacteria (Chen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…), which are the source and sink of particles, respectively. Quite a few studies have been carried out to evaluate the performance of the air cleaner (Nelson et al 1993; Ongwandee and Kruewan 2013;Ardkapan et al 2014;Zhang et al 2010;Kang et al 2008;Chen et al 2010;Jin et al 2015;Qian et al 2010). The investigations indicate that the position of the air cleaner is a key parameter, which influences the airflow patterns and leads to different removal efficiencies (Zhang et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that ESPs were able to achieve more than 50% efficiency for UFPs (ultrafine particles). Ardkapan et al [70] evaluated five portable air cleaning technologies, including an ESP with an airflow rate of 300 m 3 /h in order to determine the effectiveness of the cleaners in removing UFPs. Measurements were carried out in a test chamber.…”
Section: Short-term Studies Of Esps In Chambersmentioning
confidence: 99%